Pengaruh Medıa Anıması Terhadap Hasıl Belajar Sıswa Kelas V Sekolah Dasar - Budianti, Yudi; azisabdul, Dede (Elementary Teacher Education Program, Majalengka University, 2023)
Animation with class students who do not apply animation media, and to find out students' perceptions of the use of animated media in learning. Animation that does not implement animation media as a tool in the learning process. Delivering material. This research is a quantitative study conducted. The type of experiment used in this study was a quasi-experimental using the Nonequivalent Control Group design. Design). The sample size utilized in this study consisted of 67 students. Technique The data collection process involves the utilization of a 15-item multiple-choice test and documentation. Based on the findings of this research, the calculated t-value (4.672) exceeds the critical t-value (ttable). The obtained p-value of 0.461 indicates that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted at a significance level of 0.05. In this context, it can also be observed through a comparison of the average scores of students' academic achievement before and after the intervention. In order to apply animation media, a calculation is performed to change the number 54.66 to 75.56. The statistical analysis employed in this study is a sample t-test. Thus, it can be concluded that the instructional media in the form of Influence animation can influence student learning outcomes in class V SDIT Patriot, Bekasi Regency.